Factors Affecting the Event of Stunting - Rizky Ichwansyah; Asrul Asrul (Jurnal Perilaku Kesehatan Terpadu, 2022)
In 2022, the study population consisted of all mothers of children under the age of five who visited the stunting locus area for health screenings. This study's sample consisted of 120 participants: 60 cases and 60 controls. Total sampling was employed as the sampling method. Analysis of data using the chi-square and multiple logistic regression tests. According to the results of the bivariate analysis using the chi-square test, two variables were significantly associated with the prevalence of stunting: mother age (p = 0.012) and history of prenatal examination (p = 0.047). The results of the multivariate analysis with multiple logistic regression test revealed that there were 3 variables that influenced the incidence of stunting in children under the age of five, namely the maternal age variable with a p value of 0.001, the birth spacing variable with a p value of 0.018, and the history of pregnancy examination variables with a p value of 0.018, with the mother's age variable being the most influential variable with an odds ratio (OR) value of 1.02. Participating in the Nutrition Awareness Family program reduces the incidence of stunting among women who plan a pregnancy throughout adulthood (20-35 years) and set a safe birth spacing of more than 2 years between pregnancies. As well as consistently doing prenatal checks (> 4 times) and using the Nutrition Monitoring book as a source of information throughout early pregnancy, it is recommended to reduce the occurrence of stunting.